Numerical Study Of Plate Heat Exchanger For Erema Machine - Awang, Muhamad Haidar (Universiti Sains Malaysia, 2019)
Heat exchanger is a device widely used to control the temperature of the some machines.For the EREMA’s heat exchanger, the fluid used is water as a cooling fluid for the water bath.The current heat exchanger (53 plates) used in EREMA do not have enough capacity to maintain the temperature of water bath at 20˚C. The plan is to add more plates to the heat exchanger. The capacity of the new heat exchanger designed by HISAKAWORKS S.E.A Sdn Bhd (115 plates) need to be determined. The purpose of this project is to determine the outlet temperature of the new heat exchanger to be used in EREMA in order to determine the capacity of the heat exchanger. The heat exchanger is analysed numerically. The simulation is carried out using ANSYS 19.0 Fluent by one-way FSI. The outlet temperature is obtained thus the heat transfer of the heat exchanger can be calculated. Also in this study, the result is compared with the vendor’s data for validation and there are some differences are noticed.With the same boundary conditions, the outlet temperature obtained for water bath is 23 ˚C where the vendor’s data is 16 ˚C The inlets boundary condition is changed in order to obtain the required temperature for the water bath 20˚C. These result will serve as a basis for heat exchanger design to improve the heat transfer rate.